2019
DOI: 10.1002/adem.201900473
|View full text |Cite
|
Sign up to set email alerts
|

Forming Ability of Ultrafine‐Grained Aluminum Plates Processed by Incremental Equal Channel Angular Pressing

Abstract: Recently, post-severe plastic deformation (SPD) shaping processes have attracted attention because of the limited amount of data available on this topic. Herein, the formability of commercially pure aluminum plates with an ultrafinegrained microstructure processed by incremental equal channel angular pressing (I-ECAP) up to eight passes is discussed. The formability is evaluated experimentally using a cup-forming operation followed by modeling using finite element method (FEM). The drawn cups made of ultrafine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…Much attention is currently being paid to the development of methods for obtaining and processing aluminum-based alloys, ensuring the formation of an ultrafine-grained (UFG) structure in them [12]. Studies have shown that it can provide an improvement in the complex of physical and mechanical properties in a number of alloys in comparison with analogues produced using traditional technologies [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Much attention is currently being paid to the development of methods for obtaining and processing aluminum-based alloys, ensuring the formation of an ultrafine-grained (UFG) structure in them [12]. Studies have shown that it can provide an improvement in the complex of physical and mechanical properties in a number of alloys in comparison with analogues produced using traditional technologies [13][14][15].…”
Section: Introductionmentioning
confidence: 99%